Impact of employee value proposition on employees’ intention to stay: moderating role of psychological contract and social identity - Asha Binu Raj (South Asian Journal of Business Studies, 2021)
Purpose>This paper aims to examine the relationship between employee value proposition (EVP) and employees’ intention to stay and analyse how psychological contract and social identity moderate this relationship.Design/methodology/approach>The study was conducted in Indian IT sector among a sample of 268 employees using criterion sampling. Data were collected through structured questionnaires which revealed employees’ perceptions of EVP, intention to stay, psychological contract and social identity.Findings>The empirical results reveal that employees have greater intention to stay when their organisations deliver an EVP including development value, social value and economic value. Findings indicate that psychological contract positively strengthens the impact of EVP on employees’ intention to stay. Also, when employees strongly identify with their organisation’s image, they have higher intention to stay in presence of a strong EVP.Research limitations/implications>Consistent with the existing literature, the paper contributes an integrative model of EVP based on social exchange process, moderated by social identity and psychological contract. As the study was limited to Indian IT sector, cross-sectional nature of data is a limitation for drawing inferences about the influence or causality in general.Practical implications>The study provides a new perspective to managers to develop an attractive EVP to gain employees’ increased intention to stay. Employers in IT sector may adopt this comprehensive model to strategise their value propositions.Originality/value>This paper proposes a validated conceptual framework of EVP and intention to stay, tested for moderation effects by psychological contract and social identity. This moderation model based on social exchange adds value to employer branding literature.